Quantitative assessment of the ischemic damage to the brain parenchyma in patients with acute cerebrovascular accident using the Olea Sphere automated software - E. P. Yasakova; E. G. Shevchenko; V. V. Efimov; E. I. Zyablova (Инновационная медицина Кубани)
Objective: To evaluate the capabilities of the Olea Sphere automated software for the quantitative assessment of ischemic damage to the brain parenchyma during computed tomography (CT) in patients with acute cerebrovascular accident and its role in choosing the optimal treatment strategy in everyday clinical practice.Materials and methods: We retrospectively analyzed the data from 129 patients with suspected stroke who underwent perfusion CT within 24 hours of admission to the hospital. The Olea Sphere data were used to assess the volume of the infarct core, which was defined as an area with a relative cerebral blood flow less than 40%, the volume of the penumbra area, where Tmax exceeded 6 s, and ultimately the core-penumbra ratio.Results: With the Olea Sphere automated software, we were able to assess the volume of the ischemic changes in the brain parenchyma, particularly, the average volume of the infarct core in 129 patients was 21.95 (1-206) ml, the average volume of the penumbra area was 57.01 (2-357) ml, the core-penumbra ratio was 2.65, and mean time from CT to the start of treatment was 1.2 (0.9-1.9) hours. This quantitative data processing powered by the Olea Sphere provided the indications for the following endovascular treatment in patients with stroke: thrombus extraction in the acute period was performed in 51 patients (72.8%), transluminal balloon angioplasty with stent placement – in 12 patients (17.1%), and carotid endarterectomy in the long-term period – in 5 (9.6%) patients.Conclusions: We discovered that the Olea Sphere automated software can be used to assess ischemic changes in the brain and to make decisions related to patients with acute cerebrovascular accident in emergency conditions.